2017
DOI: 10.1111/joor.12593
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of swallowing ability using swallowing sounds in maxillectomy patients

Abstract: Maxillectomy for oral tumours often results in debilitating oral hypofunction, which markedly decreases quality of life. Dysphagia, in particular, is one of the most serious problems following maxillectomy. This study used swallowing sounds as a simple evaluation method to evaluate swallowing ability in maxillectomy patients with and without their obturator prosthesis placed. Twenty-seven maxillectomy patients (15 men, 12 women; mean age 66.0 ± 12.1 years) and 30 healthy controls (14 men, 16 women; mean age 44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…In our preliminary pilot study, we obtained sampling sounds at several different sites, including the lateral side of the cricoid cartilage and above the sternocleidomastoid muscle, but the analysis was affected by noise generated by friction between the skin or clothes and the electronic stethoscope during swallowing movements. Similar noise may have affected analyses in previous studies using laryngeal microphones (Jayatilake et al, 2015;Kamiyanagi et al, 2018). The sternal notch is a good landmark and serves as a stable site for auscultation, and this may be a factor in the relative stability of measurements from recordings made with the electronic stethoscope at the top of the sternum compared with the results of previous studies using recordings made with a laryngeal microphone at the side of the neck.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In our preliminary pilot study, we obtained sampling sounds at several different sites, including the lateral side of the cricoid cartilage and above the sternocleidomastoid muscle, but the analysis was affected by noise generated by friction between the skin or clothes and the electronic stethoscope during swallowing movements. Similar noise may have affected analyses in previous studies using laryngeal microphones (Jayatilake et al, 2015;Kamiyanagi et al, 2018). The sternal notch is a good landmark and serves as a stable site for auscultation, and this may be a factor in the relative stability of measurements from recordings made with the electronic stethoscope at the top of the sternum compared with the results of previous studies using recordings made with a laryngeal microphone at the side of the neck.…”
Section: Discussionmentioning
confidence: 86%
“…Several similar previous studies also evaluated swallowing sounds using a microphone and analyzed their wavelengths, sound pressure, and duration using acoustic analysis software to assess swallowing function; however, research on swallowing sounds has been somewhat unclear; there is a lack of studies on quantitative swallowing strength change assessments due to factors such as sex and posture (Jayatilake et al, 2015; Kamiyanagi et al, 2018). However, we combined the INDEX and swallowing sound pressure (RMS) to compare differences between sexes, postures, and liquid volumes and found that differences in the INDEX were detected between sexes and postures (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible to provide an immediate surgical obturator in collaboration not only with oral, head and neck, and plastic surgeons in the same hospital, but also with other hospitals [10]. A notable and useful point is to provide an immediate surgical obturator, reduce contamination of the surgical wound, and enable relatively normal speech [11] and swallowing [12] in the immediate postoperative period. It is also advantageous because wearing an immediate surgical obturator shortens the period of tube feeding and enables early initiation of oral nutrition [13].…”
Section: Introductionmentioning
confidence: 99%
“…Swallowing is equally important for well-nutrition, whereas it must be an extremely complex neuromuscular process [11,12]. In maxillectomy patients, swallowing is often impaired by resection and radiotherapy [13][14][15][16] and previous studies evaluated the effect of maxillofacial prostheses on swallowing after maxillectomy [16][17][18][19][20][21][22], although functional impacts of maxillofacial prostheses remain controversial because multiple variables are related to swallowing. However, it is obvious that tongue functions play a crucial role in swallowing, especially during oral and pharyngeal phase [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%